Experimental and density functional theory studies on benzalkonium ibuprofenate, a double active pharmaceutical ingredient. (February 2018) - Safna Hussan, K.P.; Thayyil, M. Shahin; Rajan, Vijisha K.; Muraleedharan, K.
Graphical abstract: Highlights: Studies on a double active pharmaceutical ingredient benzalkonium ibuprofenate. Predicted aromaticity, delocalization effects & stabilization energy via NBO analysis. BaIb is stable with better biological activity than its parent drugs. Ib- is an excellent precursor for the synthesis of double active pharmaceutical ingredient. Abstract: Molecular aspects of a double active pharmaceutical ingredient in ionic liquid form, benzalkonium ibuprofenate (BaIb), were studied using density functional theory (DFT/B3LYP/6-31+G (d, p)). A detailed discussion on optimized geometry, energy, heat and the enthalpy of BaIb was carried out. The computed vibrational results agree well with the experimental results. The stability and biological activity were compared to the parent drugs on the basis of global descriptive parameters. The electrophilic and nucleophilic sites were pointed out in the MESP structures well evidently. NBO analysis was also done to predict the relative aromaticity, delocalization effects and the contribution towards stabilization energy of the title compound. The information about non-covalent, non-ionic weak interaction between the cation and anion was obtained from the list of Mulliken charges and NBO analysis.